(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Tuberculosis (TB) is a threat to global and regional health security, that the fight against the disease has been a long and difficult battle. Despite best efforts, the TB burden is still unacceptably high. This research work’s objective is to provide a framework for health stakeholders in TB prevention and control at the community level. It aimed to determine the extent of health practices and the extent that factors affect health practices in TB prevention and control. The researcher utilized the descriptive –survey method of research. Purposive sampling was used in the selection of the respondents, which included 134 residents from Candon City, Ilocos Sur. It was found that the respondents frequently carry out relevant health practices in fighting for tuberculosis in terms of their nutrition, hygiene, rest and exercise, and lifestyle, which were moderately affected by the client, health system, and therapy-related factors. Lastly, the therapy-related factors were found to be significantly related to nutrition; but the rest of the variables were not. With the findings of this study, it is interesting to review existing information and communication materials for possible revisions or development of new IEC materials toward TB prevention and control. Furthermore, a similar study in other areas with a wider scope and population should also be considered.